Keanekaragaman dan fluktuasi kelimpahan Collembola di sekitar tanaman kelapa sawit di perkebunan Cikasungka, Kabupaten Bogor - Erwinda Erwinda; Rahayu Widyastuti; Gunawan Djajakirana; Yayuk Rahayuningsih Suhardjono (Jurnal Entomologi Indonesia, 2016)
Collembola is one of the dominant microarthopods in almost all soils types. They have important function in food webs soil ecosystem. This research was done at Cikasungka oil palm plantation for six months (April until September 2014). The aim of the research was to collect the information of diversity abundance and population fluctuations of Collembola, and their linkages between environmental factors. Collembolans were collected based on four points of soil sample from five trees of oil palm which has similar criteria. Distance of 0, 120, 240 cm from the trees, and compost lane were used to collect the samples. Results showed 37 species from 10.438 individuals with a density of 544 individu/m2. The species belongs to  4 orders and 13 families. Result also showed that are fluctuations in the abundance at the sample sites. The highest abundance of Collembolans was found in base tree zone (920 individu/m2) and compost lane (763 individu/m2). During six months, total populations of Isotomid sp. 5 (Isotomidae) was higher than the others species of Collembolans. Based on the correlation analysis, various species of Collembolans are positively correlated with rainfall and soil pH.